Sugar lowering in fermented apple-pear juice orchestrates a promising metabolic answer in the gut microbiome and intestinal integrity - Ali Zein Alabiden Tlais; Andrea Polo; Lena Granehäll; Pasquale Filannino; Olimpia Vincentini; Francesca De Battistis; Raffaella Di Cagno; Marco Gobbetti (Current Research in Food Science)
Excessive sugar consumption in young people, who are the major consumers of sugary drinks, combined with limited physical activity, is an important determinant of obesity. Despite their natural appeal, fruit juices have a similar sugar content to that of sugary drinks and once metabolized, they may induce the same biological response. This study aimed to verify whether fermentation processes can make juice consumption healthier and whether reduced-sugar juices have a specific impact on intestinal function. We designed a tailored fermentation of apple-pear juices with lactic acid bacteria and yeasts, which resulted in a reduction of sugar content (27–66%) and caloric intake, and an increase in mannitol content. The impact of newly developed apple-pear juices on gut microbiome composition and functionality was evaluated in vitro using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME). Promising changes were found in the gut microbiota and its metabolic responses and functionality, targeting pathways related to obesity and weight loss (lipopolysaccharide and secondary metabolite biosynthesis, polycyclic aromatic hydrocarbon degradation, and amino sugar and nucleotide sugar metabolism). Additionally, the fermented apple-pear juices positively modulated the intestinal epithelial features. While the simulation of the study simplifies the complex in vivo conditions, it suggests that low-sugar fermented apple-pear juices can elicit targeted responses in the gut ecosystem, contributing to healthier alternatives to traditional fruit juices.